Aging in Different Welfare Contexts: A Comparative Perspective on Later-Life Employment and Health. (19th March 2019) - Madero-Cabib, Ignacio; Corna, Laurie; Baumann, Isabel
Abstract: Objective: We adopt a cross-national comparative perspective to assess the labor market experiences of older adults in the years leading up to and beyond the full pension age (FPA) and their association with health in diverse welfare state contexts. Method: We work with a harmonized pooled-country data set of 12 nations to model individuals' employment trajectories during the 10 years surrounding gender- and country-specific FPAs over the same chronological period (2004 to 2014/2015) using sequence analysis. We then analyze these trajectories' relationships with self-rated health and chronic conditions across different welfare state contexts. Results: We find five types of later-life employment trajectories: early retirement, conventional retirement, predominantly part-time, not in the labor market, and partial retirement . Among other findings, our analyses indicate that early retirement is associated with positive health outcomes in social-democratic and corporatist countries but not in liberal and liberal-corporatist countries. For people in the not in the labor market trajectory, poor self-rated health is more frequent in liberal and southern, and less frequent in corporatist countries. Discussion: The research findings illustrate the importance of both generous public benefits in old age and later-life employment trajectories for older individuals' health.